FORMATION OF AMATEUR SCRIPTS ABILITY OF STUDENTS OF THE INSTITUTE OF CULTURE AND ARTS (Scientific journal of the Fergana State University, 2023)
This article provides pedagogical advice on the development and improvement of the ability to write amateur scripts in the Institute of culture and art. Basically, special emphasis was placed on the specifics of the creative  work of students. So that the script (amateur or professional) requires a person to have a special potentials. And the ability of creative students can be polished and perfected by educators in the field. At the same time, pedagogical recommendations and suggestions are given.